Agent-based macroeconomics and classical political economy: Some Italian roots - Giovanni Dosi; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
In this work, we discuss how the rich academic milieu left by different Italian political economy traditions after WWII paved the way to the development of a new generation of macroeconomic agent-based models. The K+S (Dosi et al., 2010, 2016a), CATS (Delli Gatti et al., 2005, 2011) and EURACE (Cincotti et al., 2010; Teglio et al., 2012) families of agent- based models are at the frontier of an alternative macroeconomic research paradigm which considers the economy as a complex evolving system. The three families of models are presented in details and their empirical performance and policy exercises discussed.
Keywords: B22; B5; E00; E32; E6; O3; O4; 330; Agent-Based Macroeconomics; Classical Political Economy; Macrodynamics; Complexity Theory; L. L. Pasinetti; P. Sylos Labini